2020
DOI: 10.7150/thno.50992
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced p38 MAPK activation facilitates viral infection

Abstract: Rationale: Many viral infections are known to activate the p38 mitogen-activated protein kinase (MAPK) signaling pathway. However, the role of p38 activation in viral infection and the underlying mechanism remain unclear. The role of virus-hijacked p38 MAPK activation in viral infection was investigated in this study. Methods: The correlation of hepatitis C virus (HCV) infection and p38 activation was studied in patient tissues and primary human hepatocytes (PHHs) by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 44 publications
3
65
0
Order By: Relevance
“…For example, SFTSV triggers mitochondrial dysfunction and NLRP3 inflammasome activation [ 38 ]. Moreover, the virus activates p38 mitogen-activated protein kinase (MAPK) signaling pathway [ 39 ], which plays a crucial role in many biological processes, such as cell proliferation and apoptosis, inflammation, aging and tumorigenesis [ 40 , 41 , 42 ]. Additionally, SFTSV causes a global disruption of naïve T-cell differentiation, and antibody class switching [ 34 ], resulting in impeded humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SFTSV triggers mitochondrial dysfunction and NLRP3 inflammasome activation [ 38 ]. Moreover, the virus activates p38 mitogen-activated protein kinase (MAPK) signaling pathway [ 39 ], which plays a crucial role in many biological processes, such as cell proliferation and apoptosis, inflammation, aging and tumorigenesis [ 40 , 41 , 42 ]. Additionally, SFTSV causes a global disruption of naïve T-cell differentiation, and antibody class switching [ 34 ], resulting in impeded humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the observed effects of MAPK inhibitors on MAYV replication did not appear to result from virucidal activity by these compounds. Previous reports have shown that p38 inhibition affects the replication of viruses from different families, among them, enterovirus 71, hepatitis C virus, influenza virus, Chikungunya virus and SARS-CoV-2 [27,35,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of TAB1-dependent p38 activation impaired hepatitis C virus (HCV) assembly and viral replication. This was also confirmed for severe fever with thrombocytopenia syndrome virus (SFTSV), herpes simplex virus type 1 (HSV-1), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 127 ]. Indeed, the p38 inhibitor losmapimod is currently in a clinical trial to treat SARS-CoV-2 (ClinicalTrials.gov ID: NCT04511819).…”
Section: Pathophysiological Implications Of Atypical P38 Signalingmentioning
confidence: 92%